The Role of Health Administration and Coordination among Emergency Services, Nursing, Dentistry, and Social Work in Enhancing the Effectiveness of Toxicological Interaction Analysis - Hatem Marzwq Hadi Al Monajam; Hagaba Ali Saleh Alyami; Fares Mohamad Al Monajam; Abdullah Mohammed H Alyami; Mushabbab Ali Saleh Alyami Khabash; Ibrahim Mohammed H Alyami Badr; Mahdi Hussain Almunajim; Mohamed Owaid Mahdy Soliman; Ali Mohammed Mohammed Al Hatailah; Hadi Jahwil Al Mansour; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Toxicological emergencies demand a coordinated, interdisciplinary approach to ensure effective prevention, diagnosis, and management. This review highlights the critical roles of health administration, emergency services, nursing, dentistry, and social work in addressing toxicological interactions and enhancing patient outcomes.Poisoning incidents, whether intentional or accidental, present a significant global health challenge, necessitating cohesive strategies for prevention, diagnosis, and management. Health administrators streamline toxicological services by implementing policies, integrating regulatory standards, and leveraging health information technologies such as electronic health records and decision-support systems. Emergency services stabilize patients and manage acute exposures through systematic approaches, while nurses contribute through continuous monitoring, education, and the application of decontamination techniques. Dentists provide critical insights into the oral manifestations of toxicity, often serving as early detectors of systemic exposures. Social workers address the psychosocial determinants, advocating for resource accessibility and long-term solutions.